Gaseous plume diffusion characteristics within model PEG canopies: Task IIB research technical report, Deseret Test Center - Meroney, Robert N., author; Kesic, Dragoljub Mile, author; Yamada, Tetsuji, author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1968)
A point source of an air-helium mixture was released continuously at various positions within a simulated canopy composed of 9 cm high pegs, 0.48 cm diameter, spaced in several arrays (2.54 x 2.54, 3.55 x 3. 55, and 5.08 x 5.08 cm). Variations of the vertical location of the source revealed the strongly non isotropic character of diffusion within a canopy with respect to the relative diffusion rates in the lateral and vertical directions. When the source was placed at various downstream distances from the edge of the canopy, it displayed a tendency to exhale the plume near the front of the model canopy and to inhale the plume at distances further downstream. Calculations of tile turbulent diffusion coefficient, K, within and above the canopy from the experimental data, reveal both a constant region and a region of linear increase with height increase as suggested by previous author.
CER68-69RNM-DK-TY-3.
September 1968.
Wind tunnel studies and simulations of turbulent shear flows related to atmospheric science and associated technologies.
For Atmospheric Science Laboratory, U.S. Army Electronics Command, Fort Monmouth, N.J.
Keywords: Wind tunnels; Turbulent diffusion (Meteorology)